Membangun sistem informasi Posyandu berbasis web pada Puskesmas Pengaringan menggunakan PHP dan MySQL - Hartati, Sri; Rusidi, Rusidi (Universitas Lembah Dempo, 2021)
Technology cannot be separated from the activities of everyday life. Technology is needed in all fields in an effort to achieve easy completion of work. One technology that is rapidly developing is the internet. Internet is part of information technology whose existence continues to grow from year to year. The large number of needs for convenience in making work easier, accompanied by an increase in internet users. The internet is used in various fields, one of which is the health sector. In the field of health, the internet is used among other things as a medium for health information. The internet is used as a medium of information, one of which is the website. A website is a tool that contains information displayed by browsers, such as Mozilla Firefox, Google, Chrome, or others. The website also provides added value as an international scope that can be accessed by everyone in the world. Apart from providing information there is also a web-based information system. One of the web-based information systems used in the health sector is the posyandu information system. The posyandu information system is designed to record posyandu activities that are routinely carried out at the Puskesmas as the closest health center in the community. Several methods are used to obtain the required data. Among other things, Interview, Observation Method, and Reference Method. In this study, a laptop unit with laptop specifications and software for Windows 10, PHP and MySQL, XAMPP and Visual Studio Code were used. The results obtained from this research are in the form of Information Systems. This system is called the web-based Posyandu information system at Puskesman Pengaringan. Keywords: Internet, Website, Posyandu.